2016
DOI: 10.1111/sms.12773
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and academic performance in youth: A systematic review

Abstract: Physical fitness (PF) is a construct of health‐ and skill‐related attributes which have been associated with academic performance (AP) in youth. This study aimed to review the scientific evidence on the association among components of PF and AP in children and adolescents. A systematic review of articles using databases PubMed/Medline, ERIC, LILACS, SciELO, and Web of Science was undertaken. Cross‐sectional and longitudinal studies examining the association between at least one component of PF and AP in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
193
3
23

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(235 citation statements)
references
References 95 publications
(279 reference statements)
16
193
3
23
Order By: Relevance
“…The overall positive relationship between school‐level cardiorespiratory fitness performance and scores on academic tests for all participants is consistent with previous results at the individual and school level. School‐level studies from Texas similarly found a positive association between cardiorespiratory fitness and academic achievement, controlling for SES and BMI .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The overall positive relationship between school‐level cardiorespiratory fitness performance and scores on academic tests for all participants is consistent with previous results at the individual and school level. School‐level studies from Texas similarly found a positive association between cardiorespiratory fitness and academic achievement, controlling for SES and BMI .…”
Section: Discussionsupporting
confidence: 90%
“…Schools in the United States are under pressure to boost academic achievement, as school funding and autonomy depend upon meeting school‐level academic standards . In light of the encouraging fitness‐academics body of literature, promoting physical fitness in schools could be a viable strategy to meet academic targets. It may be inappropriate, however, to infer that the fitness‐academics pattern observed at the student level is the same as the pattern at the school level, due to potential for the atomistic fallacy, or inappropriate inference that individual‐level patterns hold at the group level .…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Usamos regresiones lineales múltiples ajustando por edad, sexo, índice de masa corporal y nivel de estudios de las madres, para observar la relación entre cada componente de condición física, y el rendimiento escolar. Nuestros hallazgos van en la línea de la literatura previa, y muestran que una mayor condición física se asocia con mejor rendimiento escolar (Santana et al, 2016). La práctica de AF aumenta la producción de irisina en el músculo, una proteína que es clave para el cerebro y el aprendizaje.…”
unclassified